2016
DOI: 10.1016/j.jvs.2015.12.059
|View full text |Cite
|
Sign up to set email alerts
|

The Gore Hybrid Vascular Graft in renovisceral debranching for complex aortic aneurysm repair

Abstract: we analyzed outcomes of 13 patients who underwent open surgical debranching of renovisceral vessels for thoracoabdominal aortic aneurysm and PAAAs. All patients were considered at high risk for conventional surgery. Inclusion criterion was treatment by open surgical debranching of at least one visceral artery (renal artery, superior mesenteric artery [SMA], or celiac trunk [CT]) using the GHVG. In a second step, the aortic stent graft was implanted to exclude the aneurysm. If required, parallel grafts to the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…Whereas the long-term outcomes of GHVG remain to be seen, multiple authors have reported excellent short-term patency (92%-94%) of visceral vessels treated in this manner 8, 18. Important limitations of this technique include the risk of autonomic nerve injury due to CIA dissection (particularly on the left), risk of iliocaval injury, high EBL, and long operative time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas the long-term outcomes of GHVG remain to be seen, multiple authors have reported excellent short-term patency (92%-94%) of visceral vessels treated in this manner 8, 18. Important limitations of this technique include the risk of autonomic nerve injury due to CIA dissection (particularly on the left), risk of iliocaval injury, high EBL, and long operative time.…”
Section: Discussionmentioning
confidence: 99%
“…A physician-made hybrid vascular graft created by sewing endovascular iliac limbs to the limbs of a conventional polyester bifurcated graft has previously been described to reduce operative time during open abdominal aortic aneurysm repair and could be applicable to a robotic approach 5 . The Gore Hybrid Vascular Graft (GHVG; W. L. Gore & Associates, Flagstaff, Ariz) has been used to revascularize vessels in difficult locations, such as the distal internal carotid artery,6, 7 as well as renal and visceral arteries during thoracoabdominal repair 8 . Combining this sutureless anastomotic technique with the robotic approach allows us to access, control, and reconstruct the iliac system more easily as it greatly facilitates deep pelvic dissection and circumferential vessel anastomosis.…”
mentioning
confidence: 99%
“…Generally, one should also have in mind the Vortec technique to reduce the number of anastomoses; in this method a self-expanding stent-graft is deployed in the target vessel using the Seldinger technique and then is anastomosed to the graft, reducing the operating and flow cessation time to the viscera. 30 Interestingly, a common disadvantage of the method encountered is the appearance of endoleaks. 23 In a recent study, a reintervention rate of 12% after hybrid repair due to endoleaks has been emphasized.…”
Section: Hybrid Taaa Repairmentioning
confidence: 99%
“…Hybrid repair can be a valid alternative and is more often considered since the VORTEC technique was first described [14]. In the examined amount of time, we only used this technique once.…”
Section: Hybrid Proceduresmentioning
confidence: 99%